Subcellular localization of adenosine A1 receptors in nerve terminals and synapses of the rat hippocampus - Rebola, Nelson (2003)
Adenosine is a neuromodulator in the CNS that mainly acts through pre- and postsynaptic A1 receptors to inhibit the release of excitatory neurotransmitters and NMDA receptor function. This might result from a highly localized distribution of A1 receptors in the active zone and postsynaptic density of CNS synapses that we now investigated in the rat hippocampus. The binding density of the selective A1 receptor antagonist, [3H]1,3-dipropyl-8-cyclopentylxanthine ([3H]DPCPX), was enriched in membranes from Percoll-purified nerve terminals (Bmax=1839±52 fmol/mg protein) compared to total membranes from the hippocampus (Bmax=984±31 fmol/mg protein), the same occurring with A1 receptor immunoreactivity. [3H]DPCPX binding occurred mainly to the plasma membrane rather than to intracellular sites, since the binding of the membrane permeable A1 receptor ligand [3H]DPCPX to intact hippocampal nerve terminals (Bmax=1901±192 fmol/mg protein) was markedly reduced (Bmax=321±30 fmol/mg protein) by the membrane impermeable adenosine receptor antagonist, 8-sulfophenyltheophilline (25 [mu]M). Further subcellular fractionation of hippocampal nerve terminals revealed that A1 receptor immunoreactivity was strategically located in the active zone of presynaptic nerve terminals, as expected to understand the efficiency of A1 receptors to depress neurotransmitter release. A1 Receptors were also present in nerve terminals outside the active zone in accordance with the existence of a presynaptic A1 receptor reserve. Finally, A1 receptor immunoreactivity was evident in the postsynaptic density together with NMDA receptor subunits 1, 2A and 2B and with N-and P/Q-type calcium channel immunoreactivity, emphasizing the importance of A1 receptors in the control of dendritic integration.